IMPLEMENTATION OF E-GOVERNMENT ON THE E-ORDER SYSTEM TO INCREASE MICRO, SMALL, AND MEDIUM ENTERPRISES IN SOUTH JAKARTA - Asmiyanti, Reny (Jurnal Ilmu Administrasi Negara, 2023)
Study this aims for identify and understand urgency management application e-Order or online market for goods and services public for speed up SMEs growth in DKI Jakarta Province. The program aims to increase growth economy and opportunity work for SMESs DKI Jakarta Province with provide marketing online. Website development is one of the political str(web and development strategy e-government national , that is implementation systematic development _ through realistic and measurable steps _ Government website development area is the first from four layers ( web presence , interaction , transaction and transformation / integration ) within stages development Indonesian e-government for possible Indonesian people with easy access information government area and participate  in development Indonesian democracy through online media. This study use approach qualitative through interviews and studies library, this showing several thing that is first System application e-Order this is breakthrough innovative BPPBJ (Service Agency Procurement Goods and Services) Government DKI Jakarta Province Second, System Application e-Order is connecting application _ activity purchase SMES products (as supplier) with agency government province in DKI Jakarta.System building e-Order this is form cooperation Among Provincial government DKI Jakarta with citizen. DKI Jakarta residents can participate direct in the development process Technology Industry 4.0 DKI citizens must be IT -based care with IT progress, SMEs can develop marketing and owning quality more product _ fine, however permanent notice factor effective and efficient from use system   e-government.